Religious Moderation: The Concept and Practice in Higher Education Institutions - Adon Nasrullah Jamaludin (AL-ISHLAH: Jurnal Pendidikan, 2022)
This article aims to capture the concept and practice of religious moderation in higher education institutions considered modern laboratories of religion because they accommodate students across the nation with various ethnicities and religions and diverse, unique characteristics. By providing such a learning environment, higher education institutions can disseminate the meaning of the difference to students. This study employed a literature review as the research design. Six articles published in national journals were selected as the data. Those articles were analyzed thematically. The results of this study are divided into two major themes, namely, the concept of religious moderation in higher education institutions and the practice of religious moderation in higher education institutions. This indicates that the indicators initiated by the Ministry of Religion of the Republic of Indonesia as a feature of solid religious moderation in an educational institution have been practised or carried out daily. Higher education institutions, namely universities, are the leading laboratories in developing and implementing religious moderation. The results of this development are then given to other lower educational institutions and the general public.